An observational ergonomic tool for assessing the worn condition of slip-resistant shoes. (October 2020) - Beschorner, Kurt E.; Siegel, Johanna L.; Hemler, Sarah L.; Sundaram, Vani H.; Chanda, Arnab; Iraqi, Arian; Haight, Joel M.; Redfern, Mark S.
Abstract: Worn shoes are known to contribute to slip-and-fall risk, a common cause of workplace injuries. However, guidelines for replacing shoes are not well developed. Recent experiments and lubrication theory suggest that the size of the worn region is an important contributor to the shoe tread's ability to drain fluid and therefore the under-shoe friction. This study evaluated a simple test for comparing the size of the worn region relative to a common object (AAA and AA battery) as a means of determining shoe replacement. This study consisted of three components involving slip-resistant shoes: Experiment #1: a longitudinal, mechanical, accelerated wear experiment; Experiment #2: a longitudinal experiment where the same shoes were tested after each month of worker use; and Experiment #3: a cross-sectional experiment that exposed participants to a slippery condition, while donning their own worn shoes. The COF (Experiments #1 and #2); under-shoe fluid pressure (all experiments); and slip severity (Experiment #3) were compared across outcomes (fail/pass) of the battery tests. Larger fluid pressures, lower coefficient of friction, and more severe slips were observed for shoes that failed the battery tests compared with those passing the tests. This method offers promise for assessing loss in friction and an increase in slip risk for slip-resistant shoes. Highlights: The size of tread worn regions were compared with AAA and AA batteries. Shoes "passed" the test if the worn region was smaller than the battery base. Shoes across three wear experiments were assessed using this test. Failed shoes led to lower friction, worse drainage, and more severe slips.